Issues of sexuality in the elderly as represented in Brazilian literature - Bruna Miclos de Oliveira; Josiane Aparecida Duarte; Hugo Henrique Alves Ferreira; Lucy Gomes Vianna; Armando José China Bezerra (Kairós Gerontologia, 2013)
This article aims to analyze how sexuality in elderly is represented in Brazilian literature, drawing a picture of it at different times. It seeks to identify the silencing of sexuality dramatic effects impacting on old age in the societies the elderly come from, as well as the way such societies use to expose the hypocrisy of human relationships.